Simulation and RTDS Hardware Implementation of SHAF for Mitigation of Current Harmonics with p-q and Id-Iq Control Strategies Using PI Controller - Mikkili, S.; Panda, A. K. (Engineering, Technology & Applied Science Research, 2011)
Control strategies for extracting the three-phase reference currents for shunt active power filters are compared, evaluating their performance under different source conditions in MATLAB/Simulink environment and also with Real Time Digital Simulator (RTDS) Hardware. When the supply voltages are balanced and sinusoidal, the two control strategies are converging to the same compensation characteristics but when the supply voltages are distorted and/or un-balanced sinusoidal, these control strategies result in different degrees of compensation in harmonics. The p-q control strategy is unable to yield an adequate solution when source voltages are not ideal. Extensive Simulations are carried out with PI controller for both p-q and Id-Iq control strategies for different voltage conditions and adequate results were presented. The 3-ph 4-wire SHAF system is also implemented on RTDS Hardware to further verify its effectiveness. The detailed simulation and RTDS Hardware results are included.